2020
DOI: 10.1017/s0959270920000519
|View full text |Cite
|
Sign up to set email alerts
|

Guiding local-scale management to improve the conservation of endangered populations: the example of Bonelli’s EagleAquila fasciata

Abstract: Summary Understanding the environmental drivers of demographic processes is a prerequisite for providing the evidence-based conservation guidance and management actions required to address management goals at population level. Human activities, to which most species are not adapted, are having an ever-increasing impact on the environment. Most policies and strategies focus on broad-scale conservation actions and disregard the fact that this type of action may not be adequate at local scale. In addition, eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…He also suggested that the proximity of electric pylons to water reservoirs contributed the most to the mortality by electrocution in the species. Similarly, in Portugal, Bonelli's Eagle was also attracted to power lines [64] and is considered to be amongst the main causes of mortality in the species throughout its breeding range [65,66]. We recommended that the relevant authorities implement the building of raptor-friendly pylons or retrofit them with preventive apparatus to avoid continued avian mortality throughout Israel.…”
Section: Discussionmentioning
confidence: 99%
“…He also suggested that the proximity of electric pylons to water reservoirs contributed the most to the mortality by electrocution in the species. Similarly, in Portugal, Bonelli's Eagle was also attracted to power lines [64] and is considered to be amongst the main causes of mortality in the species throughout its breeding range [65,66]. We recommended that the relevant authorities implement the building of raptor-friendly pylons or retrofit them with preventive apparatus to avoid continued avian mortality throughout Israel.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, at the regional level, the species has gone from being considered a “vulnerable” species to “endangered of extinction” in the Valencian Community 35 . This change in risk category was based on a population viability analysis in which, fundamentally thanks to the combined use of GPS transmitters and long-term field monitoring, it was found that the population trend is compromised in the medium and long term due to a high pre-adult and adult mortality, analogous to that reported in other neighbouring geographic regions 36 38 . In particular, since 2000, the Bonelli’s eagle population has suffered a decline of 48.6% in the region, with an observed reduction of the breeding population from 31 territories occupied in 2000 to 18 occupied in 2022 39 , 40 .…”
Section: Introductionmentioning
confidence: 95%